A Transitional Space for Raising Public Heritage Awareness: A Preliminary Study - Kamil, Erfan M; Angkasa, Zuber; Apriana, Apriana (Departement of Architecture, Universitas Islam Indonesia, 2024)
The Heritage awareness is an important element in ensuring the preservation of cultural heritage. Religion and cultural similarities are known to play an important role in heritage awareness. The problem in this research was the low awareness of the local community of their heritage, which was built from different religious cultures. In line with this, it is important to build an identity that can connect the community's religion with the religious context of the cultural heritage so that the community is aware of this heritage. This research aims to propose an architectural solution for raising public heritage awareness using religious similarity. Using literature review, the authors suggest the existence of a time tunnel that becomes a transitional space that connects people's current religious awareness with the past. The time tunnel is the context of cultural heritage in sites as well as in educational programs to raise awareness of the community's heritage as part of their identity. In general, the idea is supported by the liminality theory and threshold concept learning theory. We show the idea of using Buddhist heritage in contemporary Islamic Indonesia. These results provide concrete ideas based on architectural psychology and education and encourage the development of heritage conservation in areas that already have significant cultural differences from the communities that produce this heritage. Keywords: architectural solution; Buddhism; heritage awareness; Hinduism; Islam; time tunnel